Restoring regulation – IL-2 therapy in systemic lupus erythematosus. (1st November 2016) - Humrich, Jens Y.; Riemekasten, Gabriela
ABSTRACT: Introduction : The pathogenesis of systemic lupus erythematosus (SLE) involves an acquired deficiency of the cytokine IL-2, an essential growth and survival factor for regulatory T cells (Treg), which play an important role in the control of autoimmunity in SLE. In contrast to currently available therapies that broadly suppress the immune system, low-dose IL-2 therapy in SLE aims to compensate the pre-existing IL-2 deficiency and thus to restore a physiological state, where Treg can regain their ability to efficiently counteract autoimmunity. Areas covered : Here we summarize key findings that led to the development of this novel therapeutic concept and will highlight the key rationales for the clinical translation of low-dose IL-2 therapy in SLE. Expert commentary : The concept of low-dose IL-2 therapy in SLE has evolved from pathophysiological findings and thus can be considered a selective biological treatment strategy in SLE. Preliminary results from phase I/II studies are promising by proving selective Treg expansion and by providing first evidence for the clinical efficacy of low-dose IL-2 therapy in SLE.